Placental Changes in Eclampsia and Fetal Outcome - Rahman, MA; Rahman, MH; Habib, MA; Selimuzzaman, SM (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 191-196 The abstract of this article is available on the PubMed website